Vibration Table Test of Prefabricated L-Shaped Column Concrete Structure - Xueyan Wang; Che Chen (Buildings)
This paper conducts a full-scale shaking table test on a prototype prefabricated L-shaped column concrete house structure to experimentally verify its seismic performance in high-intensity seismic areas. We analyze the frequency of the structure, story drift angle, amplification factor of peak acceleration of ground motion, and damage distribution. The corresponding finite element model is established using ABAQUS to verify the experimental results and further study the damage forms and weak areas of the structure under a strong earthquake. The results show that the structure can maintain an elastic state under the rare intensity of a level 7 earthquake, but begins to bend and deform in the direction of the two main axes under the rare intensity of a level 8 earthquake. At a rare intensity of a level 9 earthquake, the structure is completely destroyed. This result shows that the unitary precast special-shaped column concrete structure meets the requirements of the current code.